One of the Characteristics of the Education System of European Countries is the use of the ISCED Model in the Education Sector of Uzbekistan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the educational system of European countries and its peculiarities. European education is distinguished from the education of other regions by a phased system, inclusive education, a creative approach and modern technologies. Specific aspects of the educational system of countries such as Finland, Germany, France and the United Kingdom are also explored, highlighting the importance of the Bologna Process and the credit system. In addition, there are contemporary trends in improving the quality of education, including digital education, lifelong learning, and environmental education. It serves to explore the advantages of the European education system and the possibilities of its application in our country as well.